Pengaruh Persepsi Kemudahan Dan Brand Image Toko Terhadap Niat Beli Ulang Di Online Marketplace Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Ratna Suryani; Firkhan Nur Ramdhani (Medikonis, 2022)
ABSTRACT The problem in this study is the high intention of the people of Banjarnegara in Making repeat purchases through the online marketplace. There are several factors that repurchase intention, such as : perception of ease andstore brand image. This study aims to determine the effect of perception of ease and store brand image on repurchase intentions in the online marketplace with customer satisfaction as an intervening variable. The population in this study is the Banjarnegara community of 923,192 people. While the sample of this study was 100 respondents. With purposive sampling technique. The type of data used is primary data and data collection techniques using a questionnaire via google form. The results of this study indicate that perceived ease has no positive and insignificant effect on repurchase intention. Store brand image has a positive and significant effect on repurchase intention. Perception of convenience has no negative and insignificant effect on customer satisfaction. Store brand image has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on repurchase intentions. Customer satisfaction cannot mediate the relationship between perceived convenience and repurchase intention. Customer satisfaction can mediate the relationship between store brand image and repurchase intention. Keywords: Perception of Ease, Store Brand Image, Repurchase Intention, Customer Satisfaction